Pulmonary Hypertension in Children across Africa: The Silent Threat. (30th November 2021) - Namuyonga, Judith; Mocumbi, Ana Olga
Abstract : Pulmonary hypertension (PH) is a complex puzzle in Africa, especially among children who present with a cocktail of issues including recurrent pulmonary infections, unoperated congenital heart disease, and advanced rheumatic heart disease. Sickle cell anemia and neonatal complications of transiting from fetal circulation also contribute to the burden of pulmonary hypertension. Mortality from pulmonary arterial hypertension (PAH) remains high in Africa (18-21%), claiming sufferers in the first 6 months after diagnosis. Unfortunately, PH remains underreported in sub-Saharan Africa since many centers lack the capacity to diagnose and confirm it by the recommended gold standard, right heart catheterization. The unresolved burden of unoperated congenital heart lesions and rheumatic heart disease, among other preventable causes, stand out as major causes of PH in African children. This paper highlights pediatric PAH as a result of major gaps in care and illustrates the need for its prevention as well as for the promotion of research into the most important drivers, to prevent premature mortality in the continent.